Functional Neuroimaging in Startle Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Researchers at the Epilepsy Unit, Hospital Clinic de Barcelona, Spain investigated brain areas involved in startle-induced seizures, using a functional neuroimaging approach in 4 adult patients whose seizures began at age 4 months to 10 years.